2020
DOI: 10.1016/j.annonc.2020.08.110
|View full text |Cite
|
Sign up to set email alerts
|

1237MO SAKK 16/14: Anti-PD-L1 antibody durvalumab in addition to neoadjuvant chemotherapy in patients with stage IIIA (N2) non-small cell lung cancer (NSCLC) – A multicenter single-arm phase II trial

Abstract: Background: Epidermal growth factor receptor mutation (EGFR)-tyrosine kinase inhibitor plays a key role in EGFR-mutated, metastatic non-small cell lung cancer (NSCLC). However, it has not been explored whether EGFR-TKI plus concurrent thoracic radiotherapy may be effective in locally-advanced NSCLC patients with EGFR mutation.Methods: Chemotherapy-naïve, locally-advanced NSCLC patients with EGFR mutation were enrolled. Patients were treated with gefitinib (250mg/day, p.o. for 2 years) plus concurrent thoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…None of the AEs were associated with surgery delays or deaths. Similarly, at the ESMO Virtual Congress 2020, Rothschild et al presented the findings of their phase-II clinical trial (SAKK 16/14, NCT02572843) in which standard neoadjuvant cisplatin and docetaxel combined with neoadjuvant durvalumab was used to treat patients with stage IIIA (N2) NSCLC (35). In total, 68 patients were enrolled in the study.…”
Section: Neoadjuvant Immunotherapy Combined With Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…None of the AEs were associated with surgery delays or deaths. Similarly, at the ESMO Virtual Congress 2020, Rothschild et al presented the findings of their phase-II clinical trial (SAKK 16/14, NCT02572843) in which standard neoadjuvant cisplatin and docetaxel combined with neoadjuvant durvalumab was used to treat patients with stage IIIA (N2) NSCLC (35). In total, 68 patients were enrolled in the study.…”
Section: Neoadjuvant Immunotherapy Combined With Chemotherapymentioning
confidence: 99%
“…Upon review, the MPR and pCR rates reported for immunotherapy only range from 14-45% and 0-16.2% (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Conversely, the MPR and pCR rates reported for the combination therapy of chemotherapy and neoadjuvant immunotherapy range from 15-86% and 9-63%, respectively (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Further, there is evidence that the combination therapy may lead to increased anti-tumor activity (33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Neoadjuvant Immunotherapy Combined With Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the incidence of side effects of combined and immunotherapy chemotherapy compared with immune monotherapy was higher, it was also within the tolerable range. In the SAKK 16/14 study, the proportion of patients with side effects above grade 3 was 88.1% (35). Whether the higher incidence of side effects is related to the trial design of 3 courses of chemotherapy followed by sequential 2 courses of immunotherapy still needs to be verified.…”
mentioning
confidence: 99%
“…The SAKK 16/14 study (NCT02572843) investigated 3 cycles of cisplatin/ docetaxel followed by 2 cycles of durvalumab in the treatment of stage IIIA (N2) NSCLC patients. Patients who received neoadjuvant immunotherapy had an imaging response rate (from 44.8% to 58.1%) after chemotherapy (35). Among the 55 patients who underwent surgical resection, the MPR rate was 60% (33/55) and the pCR rate was 18.2% (10/55).…”
mentioning
confidence: 99%